Fabrication of high density CdTe/GaAs nanodot arrays using nanoporous alumina masks - Jung, Mi; Lee, Hong Seok; Park, Hong Lee; Mho, Sun-il (Current applied physics, 2006)
Long-range ordered semiconductor CdTe nanodot arrays of the uniform size were formed by molecular-beam epitaxy on the GaAs substrate as a replica of the nanoporous alumina mask in spite of the large lattice mismatch between GaAs and CdTe. The number per unit area and the size of nanodots of the heterostructure semiconductor CdTe/GaAs were controlled by those of pores in the mask. Using a very thin nanoporous alumina mask (<200nm thick) prepared at the anodization voltage of 30V in oxalic acid, fabricated were the arrays of CdTe nanodots (55nm diameter) with the large number per unit area of 1.3×1010cm−2.